Accelerated Aging Ultraviolet of a PET Nonwoven Geotextile and Thermoanalytical Evaluation - Franco, Yara Barbosa; Valentin, Clever Aparecido; Kobelnik, Marcelo; da Silva, Jefferson Lins; Ribeiro, Clovis Augusto [UNESP]; da Luz, Marta Pereira (MDPI, 2022)
Nonwoven geotextiles are geosynthetic products that are highly susceptible to ultraviolet degradation because light can reach a large area of the material due to its fiber arrangement. Even with additives, which delay the degradation process, material decomposition still occurs, and therefore the product’s long-term durability can be affected. In this paper, the mechanical and thermal behavior of a commercial nonwoven polyester geotextile subjected to accelerated ultraviolet aging tests were evaluated. The deterioration was evaluated by comparing the physical properties (mass per unit area, thickness, and tensile strength) and thermal behavior (thermogravimetry—TG, thermomechanical analysis—TMA, and differential scanning calorimetry—DSC) before and after exposure times of 500 h and 1000 h. The results showed that the ultraviolet aging tests induced some damage in the polyester fibers, leading to the deterioration of their tensile strength. For 1000 h of exposure, in which the reduction was larger, scanning electron microscopy (SEM) found some superficial disruption of the fibers, indicative of damage. TG and DSC could not capture the effects of UV radiation on polymer degradation, unlike TMA. This latter technique was effective in showing the differences between specimens before and after UV exposure.
Keywords: nonwoven geotextile; physical tests; polyester; thermal analysis